Peran Kimia Medisinal Dalam Pengembangan Obat Baru - Khaerina, Yunisa; Amin, Saeful (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Medicinal chemistry plays a crucial role in the discovery and development of new, effective and safe drugs. This study aims to analyze the contribution of medicinal chemistry in the stages of drug development, from identification of target compounds to optimization of pharmacokinetic characteristics. The method used is a systematic literature review of the latest research and developments in the field of medicinal chemistry over the past ten years. The results of the study indicate that structure-based and computer-aided (in silico) approaches have significantly increased the efficiency of drug discovery, while molecular modification techniques contribute to the development of drugs with higher efficacy and minimal side effects. The analysis also identifies trends in nanotechnology-based drug development, the use of artificial intelligence, and green chemistry approaches in the synthesis of medicinal compounds. In conclusion, medicinal chemistry continues to develop as a vital discipline in facing the complex challenges of developing new drugs to overcome diseases that do not yet have adequate treatment. Further research is recommended to optimize the integration of various medicinal chemistry approaches with other interdisciplinary fields to accelerate the discovery of innovative new drugs.